The Passive as a Style Marker in Early Modern English: Evidence from the Helsinki Corpus - Elena Seoane Posse (Miscelánea: A Journal of English and American Studies, 1998)
This paper offers a description of the stylistic dimension of the passive in the Early Modern English period as represented in the computerised Helsinki Corpus of English Texts. The first section examines the stylistic factors which determine the choice of a passive over an active clause. In the second section, EModE be-passives are analysed to discover the reasons for the association between passive constructions and formal styles in that period. Statistical data drawn from the corpus reveal that in EModE the correlation between the passive voice and formal registers is not primarily due to the requirement of impersonality, as is claimed for Present-day English, and that other factors also condition the preference for passives in formal registers of English.